2019
DOI: 10.1590/1678-4324-2019180438
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Geraniol on Long Term Renal Ischemia/Reperfusion Injury in Rats

Abstract: Possible protective effects of geraniol, known as antioxidant properties, were analyzed biochemically and histologically on experimental long-term renal ischemia/reperfusion I/R injury in rats. This study used 3-4 months old male Wistar albino rats and were divided into 4 groups (n = 7) by random selection: Group I (Sham Group), Group II (I/R+SF), Group III (I/R+50 mg/kg geraniol), and Group IV (I/R+100 mg/kg geraniol). A right nephrectomy was performed in all groups under anesthesia. Groups I and II were inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…In a similar study we conducted in 2019, the effect of geraniol was evaluated against longerterm I/R (60 min/24h) damage, and geraniol was seen to have increased SOD and CAT enzyme activities. This difference monitored from the angle of SOD and CAT activities between our present study and a study we have made previously is interesting (Can, Canbek, 2019). On the other hand, there are studies showing that antioxidant enzymes decrease as a result of I/R (Singh, Chander, Chopra, 2005).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In a similar study we conducted in 2019, the effect of geraniol was evaluated against longerterm I/R (60 min/24h) damage, and geraniol was seen to have increased SOD and CAT enzyme activities. This difference monitored from the angle of SOD and CAT activities between our present study and a study we have made previously is interesting (Can, Canbek, 2019). On the other hand, there are studies showing that antioxidant enzymes decrease as a result of I/R (Singh, Chander, Chopra, 2005).…”
Section: Discussioncontrasting
confidence: 46%
“…We had investigated the protective effect of geraniol on long-term renal ischemia/reperfusion injury in our previous study. As a result of 60 minutes of ischemia and 24 hours of reperfusion, following administration of 50 mg/kg and 100 mg/kg doses of geraniol intraperitoneally; the 100 mg/kg administered dose of geraniol was observed to have a protective effect on the kidney (Can, Canbek, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Besides, an acyclic isoprenoid monoterpene contained in the volatile compounds of Distichochlamys citrea extract was geraniol. The pharmacological effects of geraniol suggest that it could be a viable medication candidate for treating a variety of diseases thanks to its anti‐cancer, anti‐inflammatory, antioxidative, antibacterial, hepatoprotective, cardioprotective, and neuroprotective properties [17–19] . Especially, the monoterpenes geraniol and geranyl acetate, volatile bioactive compounds, present in the Distichochlamys citrea and several other plants were proved to exhibit significant anticancer activities against colon cancer cells [20] .…”
Section: Resultsmentioning
confidence: 99%
“…of diseases thanks to its anti-cancer, anti-inflammatory, antioxidative, antibacterial, hepatoprotective, cardioprotective, and neuroprotective properties. [17][18][19] Especially, the monoterpenes geraniol and geranyl acetate, volatile bioactive compounds, present in the Distichochlamys citrea and several other plants were proved to exhibit significant anticancer activities against colon cancer cells. [20] In these reports, evidences indicated that they are promising for the development of new cancer therapies, thus deserving further investigations.…”
Section: Chemistryselectmentioning
confidence: 99%